Domestic Workers’ Treatment under Ethiopian and South African Laws - Dabala, Diriba Mangasha; Sefara, Abdata Abebe (Italian Labour Law e-Journal, 2020)
Today domestic workers’ treatment across the globe differs substantially depending on the availability of the appropriate legal regime and the actual implementation of these laws. It is undeniable that there are huge differences in enacting laws to ensure respect for the rights of domestic workers between Ethiopia and South Africa. On the contrary, although Ethiopia has obligations under the International Labour Organization (hereinafter referred to as the ILO) conventions and national laws, so far, Ethiopia has not adopted any legislative measures to recognize domestic workers. However, one thing certainly describes both countries in a similar vogue; that is, regardless of differences in terms of having legal regimes to protect domestic workers, a practical and close examination of the life of domestic workers on the ground in both countries appears the same it is oppressive and characterized by exploitation. Though South Africa performed better concerning formulating enactments that are pertinent to ensure the protection of the rights of domestic workers that could perhaps serve as caveats for Ethiopia yet, practically both countries are not living up to their obligations and international standards especially the ILO Convention No. 189 on Decent Work for Domestic Workers and its Antecedents, and other international human rights treaties.